Human Colonization and Infection by Staphylococcus pseudintermedius: An Emerging and Underestimated Zoonotic Pathogen - Ikechukwu Benjamin Moses; Fernanda Fernandes Santos; Ana Cristina Gales (Microorganisms, 2023)
S. pseudintermedius is a known resident of the skin and mucous membranes and a constituent of the normal microbiota of dogs. It has also been recognized as an opportunistic and zoonotic pathogen that is able to colonize humans and cause severe diseases, especially in immunocompromised hosts. Most importantly, methicillin-resistant S. pseudintermedius (MRSP), which is intrinsically multidrug-resistant, has emerged with serious public health consequences. The epidemiological situation is further exacerbated with reports of its zoonotic transmission and human infections which have been mostly attributed to the increasing frequency of dog ownership and close contact between dogs and humans. Evidence on the zoonotic transmission of MRSP from pet dogs to humans (such as dog owners, small-animal veterinarians, and other people in close proximity to dogs) is limited, especially due to the misidentification of S. pseudintermedius as S. aureus. Despite this fact, reports on the increasing emergence and spread of MRSP in humans have been increasing steadily over the years since its first documented report in 2006 in Belgium. The emergence of MRSP strains has further compromised treatment outcomes in both veterinary and human medicine as these strains are resistant to beta-lactam antimicrobials usually prescribed as first line treatment. Frustratingly, the limited awareness and surveillance of the zoonotic transmission of S. pseudintermedius have underestimated their extent of transmission, prevalence, epidemiology, and public health significance. In order to fill this gap of information, this review focused on detailed reports on zoonotic transmission, human colonization, and infections by S. pseudintermedius, their pathogenic features, antimicrobial resistance profiles, epidemiology, risk factors, and treatment. In writing this review, we searched Web of Science, PubMed, and SCOPUS databases using the keyword “Staphylococcus pseudintermedius AND humans”. A phylogenetic tree to determine the genetic relatedness/diversity of publicly available genomes of S. pseudintermedius was also constructed.